Microwave-enhanced Friedländer synthesis for the rapid assembly of halogenated quinolines with antibacterial and biofilm eradication activities against drug resistant and tolerant bacteria12. Issue 4 (10th August 2016) - Garrison, Aaron T.; Abouelhassan, Yasmeen; Yang, Hongfen; Yousaf, Hussain H.; Nguyen, Tho J.; Huigens III, Robert W.
Abstract : We disclose a microwave-enhanced Friedländer reaction that led to new antibacterials and biofilm-eradicators. Abstract : Herein, we disclose the development of a catalyst- and protecting-group-free microwave-enhanced Friedländer synthesis which permits the single-step, convergent assembly of diverse 8-hydroxyquinolines with greatly improved reaction yields over traditional oil bath heating (increased from 34% to 72%). This rapid synthesis permitted the discovery of novel biofilm-eradicating halogenated quinolines (MBECs = 1.0–23.5 μM) active against MRSA, MRSE, and VRE. These small molecules exhibit activity through mechanisms independent of membrane lysis, further demonstrating their potential as a clinically useful treatment option against persistent biofilm-associated infections.